2006
DOI: 10.1152/jn.00525.2005
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Channel Interactions Underlying Rat Subthalamic Projection Neuron Rhythmic and Bursting Activity

Abstract: A computational model of the rat subthalamic nucleus projection neuron is constructed using electrophysiological and morphological data and a restricted set of channel specifications. The model cell exhibits a wide range of electrophysiological behaviors characteristic of rat subthalamic neurons. It reveals that a key set of three channels play a primary role in distinguishing behaviors: a high-voltage-activated calcium channel (Cav 1.2.-1.3), a low-voltage-activated calcium channel (Cav 3.-), and a small curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 57 publications
1
62
0
Order By: Relevance
“…Therefore, our model can still reproduce the characteristic firing properties of STN cells shown in the original model (Terman et al 2002), such as the intrinsic spontaneous discharge and postinhibitory rebound bursting (Bevan and Wilson 1999;Bevan et al 2000), which depends on T-type Ca 2ϩ currents. Other currents identified in STN neurons (Atherton et al 2010;Barraza et al 2009;Beurrier et al 1999;Gillies and Willshaw 2006;Hahn and McIntyre 2010;Overton et al 1995;Nakanishi et al 1987) were omitted to maintain a focus on a specific putative burst mechanism, and our results suggest that these additional currents are not necessary for the experimentally observed STN bursting to occur, although they may affect its properties. In particular, we omit HCN currents that have been identified in STN neurons (Atherton et al 2010), since they are activated by synaptic inhibition and act by limiting the availability of low-threshold T-type Ca 2ϩ current, neither of which is an important feature in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, our model can still reproduce the characteristic firing properties of STN cells shown in the original model (Terman et al 2002), such as the intrinsic spontaneous discharge and postinhibitory rebound bursting (Bevan and Wilson 1999;Bevan et al 2000), which depends on T-type Ca 2ϩ currents. Other currents identified in STN neurons (Atherton et al 2010;Barraza et al 2009;Beurrier et al 1999;Gillies and Willshaw 2006;Hahn and McIntyre 2010;Overton et al 1995;Nakanishi et al 1987) were omitted to maintain a focus on a specific putative burst mechanism, and our results suggest that these additional currents are not necessary for the experimentally observed STN bursting to occur, although they may affect its properties. In particular, we omit HCN currents that have been identified in STN neurons (Atherton et al 2010), since they are activated by synaptic inhibition and act by limiting the availability of low-threshold T-type Ca 2ϩ current, neither of which is an important feature in our study.…”
Section: Discussionmentioning
confidence: 93%
“…Other currents have been characterized in STN neurons (Atherton et al 2010;Barraza et al 2009;Beurrier et al 1999;Gillies and Willshaw 2006;Hahn and McIntyre 2010;Overton and Greenfield 1995;Nakanishi et al 1987), but since they were found not to be necessary for the reproduction of the experimental results that we studied (Zhu et al 2004(Zhu et al , 2005, they were omitted from the model.…”
Section: Stn Neuron Modelmentioning
confidence: 99%
“…1B) we utilized was previously published by Gillies and Willshaw (2006), and is based on the complex dynamics and morphology of rat STN neurons. The STN morphology consists of a soma and three dendritic trees, as previously reported (Kita et al, 1983;Afsharpour, 1985).…”
Section: Stn Neuron Modelsmentioning
confidence: 99%
“…The NaP current is important in controlling both the frequency and amplitude of the slow ramp depolarization before the action potential. The Kv31 channel played a role in reducing the width of the action potential to match STN neurons as closely as possible (Bevan and Wilson, 1999;Gillies and Willshaw, 2006). KCsa currents and HVA calcium currents are responsible for the emergence of the spontaneous firing properties, intrinsic to STN neurons.…”
Section: Stn Neuron Modelsmentioning
confidence: 99%
See 1 more Smart Citation